The Mindanao peace process and ODA construction, evolution and challenges - Aguja, Mario J. (2011)
The paper presents the Official Development Assistance (ODA) extended to Mindanao by donors after the signing of the final peace agreement between the Government of the Republic of the Philippines (GRP) and the Moro National Liberation Front (MNLF) in 1996. It looks at the way the so-called ?peace dividends? were constructed by the donors to support the peace process and how the various donors evolved their respective ODA in support of the Mindanao peace process, either multilaterally and bilaterally. The study also looks at the challenges of delivering ODA and the way it responds to the challenges of peace in Mindanao.